PENGARUH AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN SERTA MOTIVASI TERHADAP KINERJA GURU DI SMAN 1 DAN SMAN 68 JAKARTA PUSAT - Hadijah Sanadi (Cakrawala Management Business Journal, 2019)
This study aims to understand accountability and improve financial management as well as partial and simultaneous motivation for teacher performance in SMAN 1 dan SMAN 68 Jakarta. The research approach is a quantitative and associative quantitative approach. Data obtained using a questionnaire. The population is 82 teachers of SMAN 1 and SMAN 68, Central Jakarta, using saturated sample techniques. Data analysis technique is statistical analysis of multiple linear regression. The results of the study, partially the accountability variable has a positive effect on teacher performance. Transparency variable does not significantly influence teacher performance. The motivation variable partially has a significant effect on performance. Simultaneously the accountability, transparency and motivation variables significantly influence teacher performance. The ability of accountability, transparency, and motivation to explain changes in teacher performance is 58.4%. Among the three variables that most dominant influence teacher performance is motivation, thus motivation is very helpful for teachers in improving their performance.